2014
DOI: 10.1038/eye.2014.223
|View full text |Cite
|
Sign up to set email alerts
|

Focal vitreomacular traction: a prospective study of the evolution to macular hole: the mathematical approach

Abstract: Purporse To determine the associated balance of forces of the vitreofoveal interface in focal vitreomacular traction evolving to full-thickness macular hole (FTMH) and to link/explain the observed changes in the context of mathematical and physics models. Patients and methods This is a multicenter, prospective, and observational case series conducted at the Vitreoretinal Department of three different referral centers. Fellow eyes of patients with unilateral idiopathic FTMH were included. Eighty-nine patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…These tractional forces result in a drawbridge elevation of the inner retina12 and are then transmitted along the oblique parafoveal Müller cells, inducing a centrifugal force on the outer retina 13 14. This pathogenic sequence explains well the mechanism of MH opening but does not predict its size 15.…”
Section: Discussionmentioning
confidence: 99%
“…These tractional forces result in a drawbridge elevation of the inner retina12 and are then transmitted along the oblique parafoveal Müller cells, inducing a centrifugal force on the outer retina 13 14. This pathogenic sequence explains well the mechanism of MH opening but does not predict its size 15.…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal traction tends to create inner foveal cysts, whereas foveal detachment is likely to be formed because of more anteriorly and posteriorly oriented traction. 17 If this theory is correct, some questions arise regarding traction direction and foveal changes being predisposing factors for FTMHs. The actual vectors acting on the foveal area caused by the PH are complex and difficult to determine.…”
Section: Introductionmentioning
confidence: 99%
“…16,19,31 Observation of cases has shown that inner retinal changes are more common and that outer retinal changes can range from subtle alterations at the level of the outer segments of the photoreceptors to outer retinal dehiscence and FTMHs. 32 Recently, however, Almeida et al 22 noted that eyes with isolated inner retinal distortion but without outer retinal changes have an apparently higher incidence of spontaneous vitreomacular separation than those with outer retinal changes.…”
Section: Figure 1 Schematic Representation Of the Focal Vmt Classificmentioning
confidence: 99%